Hubungan Tingkat Kebugaran Dengan Gejala Menopause pada Wanita Premenopause - Margaretha Kus Fitriani Fruitasari (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2021)
There is a period that must be passed by women and this period for some women is very annoying. This period is a transition period towards the cessation of menstruation or menopause. This period is called the premenopausal period, which is a period of declining reproductive function, hormonal changes, physical changes, and psychological changes. The complaints of these premenopausal women are the presence of premenopausal symptoms such as: easily tired, often wake up at night or insomnia, hot flushes, night sweats, decreased memory, easy anxiety, depression, irritability and decreased body fitness level. The existence of premenopausal symptoms that greatly interfere with the quality of life of premenopausal women including a decrease in the level of body fitness makes researchers want to know whether there is a relationship between the level of body fitness with menopausal symptoms in premenopausal women. To find the relationship between fitness level and menopausal symptoms in premenopausal women. The method used in this study is an observational method of cross-sectional design (cross sectional). The subjects of this study were 96 premenopausal women in Sukajaya Village, Palembang. Data collection of premenopausal symptoms used a premenopausal symptom questionnaire and measurement of fitness level using the Kasch Step Test method. Analysis of correlation data using the Kendall Tau test. Research conducted on 96 premenopausal mothers and the results of the analysis showed a relationship between fitness level and menopausal symptoms with a value of p = -0.56, i.e. the higher the level of fitness, the lower or not felt by premenopausal women. There is a relationship between the fitness level of premenopausal women with menopausal symptoms in premenopausal women